SENGKETA TANAH PARTIKELIR DI JAWA SETELAH BERLAKUNYA UU NO. 1 TAHUN 1958 - Darini, Ririn; Ekayati, Avrilia Wahyu (Estoria: Journal of Social Science and Humanities, 2023)
This article discusses post-colonial private land policies. Private land became colonial owned land (VOC) which was given voluntarily to people who were considered meritorious for the Netherlands (former VOC employees, camat). The main problem is related to land disputes over changes in private land ownership after Law No. 1 of 1958 concerning the abolition of private land. The purpose of this article is to describe the problems that arose after the private land policy was abolished and to describe the status of ex-private land ownership rights to the property of the state or individuals and to analyze the solutions to these problems. Using historical methods and a statutory approach, this article is compiled based on the primary and secondary data obtained and then described and presented in systematic writing to answer the problem. From the results of the research, it was concluded that the problem arose due to the conversion of ex-private land into individual or state property which was determined in accordance with the terms and regulations that were in force.